MYOPIA, KOMODIFIKASI DAN MEMBANGUN PARADIGMA PENELITIAN KONSTRUKSIONIS DI INDONESIA - Nurmoko, Aditya Hera (PRIMA EKONOMIKA, 2020)
This article will discuss research myopia in Indonesia as a problem that can beovercome by the commodification of research that supports each other betweenquantitative and qualitative research, balanced so that not only the theory test exists, buttheories born of Indonesian academics are available to be tested by Indonesians andoutside in an effort to build a constructionist research that is building own theories thatare not independent of the west and are able to fill continuity, critical and advanced forthe future.Keywords: Myopia, Commidification, Paradigm